“I am a freak of nature”: Tourette’s and the Grotesque in Jonathan Lethem’s Motherless Brooklyn - Pascale Antolin (Transatlantica)
This article analyzes Jonathan Lethem’s neuronovel, Motherless Brooklyn (1999) in the light of Mikhail Bakhtin’s theory of the grotesque and laughter. The specificity of the novel lies the first-person narrator and leading character suffering from Tourette’s syndrome and appropriating the nickname “freak of nature” he was given as a child. Thereby, he plays a double role: he is both “the grotesque freak” exhibited on the platform / page, and the freakshow talker constructing the freak from his condition. The novel turns into a freakshow, not in the sense of the sordid spectacle of the past, but as a construction questioning both the social and the literary order. Through the grotesque and laughter, Lethem challenges the traditional representation of disability—and the stereotype of the disabled person—and also the major genres his novel borrows from: detective fiction and the coming-of-age narrative. The book turns into parody, in the Bakhtinian sense, i.e., both a homage to and a rewriting of traditional genres. Lethem also takes advantage of his narrator’s symptomatic verbal outbursts and penchant for grotesque images and word play to shift disability paradigm—turning stigma into asset—and revitalize illness literature.